2013
DOI: 10.1159/000343850
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials in Hepatocellular Carcinoma: An Update

Abstract: The success of sorafenib has spurred an explosive increase of clinical trials testing novel molecular targets and other agents in the treatment of hepatocellular carcinoma (HCC). The paradigm of the studies has been characterized by three noticeable changes. First, the molecular targets of interest have expanded from angiogenesis to cancer cell-directed oncogenic signaling pathways for advanced HCC treatment. Agents targeting EGFR, FGFR, PI3K/Akt/mTOR, TGF-β, c-Met, MEK, IGF signaling, and histone deacetylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 41 publications
(60 reference statements)
0
55
0
Order By: Relevance
“…Therapies targeting epigenetic modifiers, such as DNA methyltransferases or histone deacetyl ases, are an attractive approach. 133 A phase I trial of the histone deacetylase inhibitor vorinostat for treatment of patients with HCC is currently being developed, and a phase II trial investi gating another histone deacetyl ase inhibitor, belinostat, detected modest antitumour activity in 42 patients with HCC. 134 A subgroup analysis of 38 patients showed that those with high immuno reactivity to the UV excision repair protein RAD23 homologue B (HR23B)-a reported predictive response biomarker to HDAC inhibitors 135 -had a higher rate of disease stabilization.…”
Section: Met Signallingmentioning
confidence: 99%
“…Therapies targeting epigenetic modifiers, such as DNA methyltransferases or histone deacetyl ases, are an attractive approach. 133 A phase I trial of the histone deacetylase inhibitor vorinostat for treatment of patients with HCC is currently being developed, and a phase II trial investi gating another histone deacetyl ase inhibitor, belinostat, detected modest antitumour activity in 42 patients with HCC. 134 A subgroup analysis of 38 patients showed that those with high immuno reactivity to the UV excision repair protein RAD23 homologue B (HR23B)-a reported predictive response biomarker to HDAC inhibitors 135 -had a higher rate of disease stabilization.…”
Section: Met Signallingmentioning
confidence: 99%
“…These advances have led to the development of targeted therapies in HCC [9][10][11] . Nevertheless, only sorafenib, a multikinase inhibitor, remains till date the sole approved drug in advanced HCC, based on the clinical benefit observed in properly selected patients enrolled in clinical trials [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…For example codrituzumab [5], Linifarib, Sunitinib, Brivanib , cixutumumab [6][7][8][9], Everolismus showed no significant increase in overall survival (OS). Only Sorafenib as shown in the SHARP (1) trial in the West and as shown in Oriental trial conducted in the East showed statistically significant (3 months) increase in OS [10][11][12][13][14].…”
Section: Systemic Therapies In Advanced Hepatocellular Cancermentioning
confidence: 99%